Verification of a fracture model for fiber reinforced concrete beams in bending. (August 2022) - Kožar, I.; Bede, N.; Mrakovčić, S.; Božić, Ž.
Highlights: Fiber reinforced concrete failure happens through fiber pull-out. Fiber-concrete bond-slip behaviour strongly influences the failure. Crack mouth opening displacement - CMOD could be related to cross-section beam model. Numerical model is verified through experimental normalised CMOD records. Abstract: Modeling fiber-reinforced concrete at failure by fracture is a challenging task because we need insight into the post-peak behaviour of the model after failure, including crack propagation. In this paper, we present the basic properties of the fiber-reinforced concrete model and its ability to capture the phenomena in three-point bending tests. In this work, we deal with a proof of concept - the verification of the model. The verification of the code includes the selection of the optimal solution algorithm and the selection of the appropriate solution from possible pairs of solutions. Verification of the calculation includes the influence of the number of layers used in the discretisation and, in particular, the influence of the shape of the piecewise defined force–displacement curves of the layers. Only the first stage of verification was performed, i.e. qualitative comparison of the model and experimental results and the influence of the shape of the force–displacement curves. One of the most desirable features of the model is its suitability for subsequent inverse analysis and parameter determination.